Systematic studies of the sweet potato and its wild relatives - Rodriguez, P (2019)
Phylogenetic studies on the genus Ipomoea, and specifically on the species closely related to the sweet potato, have been hindered by limited taxon and character sampling. Any study that aims to investigate the phylogenetic relationships within a megadiverse genus such as Ipomoea, with an estimated 800 species, must rely on a comprehensive data set that covers as much diversity as possible, in order to provide accurate and robust phylogenetic inference. In this thesis, I present a comprehensive phylogenetic study of the genus Ipomoea and of the group of species closely related to the sweet potato using genomic-scale data. The aim of this study was to provide a phylogenetic framework with which to understand the diversity existing within the genus and to inform taxonomic decisions. The phylogenies presented here identify several recurrent patterns in the evolution of Ipomoea, for instance the multiple origin of storage roots and the existence of multiple episodes of long-distance dispersal by natural means. I also address several questions pertaining to the sweet potato that have been a matter of debate for decades but remained unanswered until recently. Our genome-scale data facilitated comprehensive phylogenies for all wild species that are most closely related to the sweet potato. Our phylogenies resolve that sweet potato is monophyletic and had a single origin, as well as identified the wild species that is its closest relative: Ipomoea trifida, with all other extant species more distantly related. In addition, our studies corroborate the existence of two sweet potato chloroplast lineages and infer that one of them resulted from a hybridisation between sweet potato and I. trifida following species divergence. Finally, I also address a question that has been of interest for over two centuries: the presence of the sweet potato, an American crop, in Polynesia in pre-European times.